1987
DOI: 10.1038/329039a0
|View full text |Cite
|
Sign up to set email alerts
|

Tetrakis(methyltelluro)tetrathiafulvalene (TTeC1TTF), a high-mobility organic semiconductor

Abstract: ChemInform Abstract The title compound (V) is prepared by consecutive treatment of tetrathiafulvalene (I) with LDA, tellurium powder (II), and methyl iodide (IV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Indeed, previous studies dealing with the tetrakis(telluromethyl)tetrathiafulvalene (MeTe) 4 TTF reported interesting results concerning the semiconducting properties of the compound in neutral state, very likely due to zigzag chains formed by Te···Te contacts. [32] The calculated band structure for complex 2, represented in Figure 5, shows a valence-band built up from the HOMO of the EDT fragment, with a dispersion of about 0.2 eV. …”
Section: Electrochemical and Theoretical Studiesmentioning
confidence: 99%
“…Indeed, previous studies dealing with the tetrakis(telluromethyl)tetrathiafulvalene (MeTe) 4 TTF reported interesting results concerning the semiconducting properties of the compound in neutral state, very likely due to zigzag chains formed by Te···Te contacts. [32] The calculated band structure for complex 2, represented in Figure 5, shows a valence-band built up from the HOMO of the EDT fragment, with a dispersion of about 0.2 eV. …”
Section: Electrochemical and Theoretical Studiesmentioning
confidence: 99%
“…61 A use of heteroatomic contacts (chalcogenÁÁÁchalcogen, chalcogenÁÁÁnitrogen) is effective to increase conductivity as observed for TTeN by Yagubskii, Neilands, Balodis, et al, 28 TTeC 1 -TTF (Fig. 8) by Inokuchi, Saito, et al, 72 BTQBT (Fig. 2) and BTDA-TCNQ (11) by Yamashita et al, 26,27,73 2,5-bis(methylthio)TCNQ (12) by Zambounis et al, 74 and bis-(ethylenethio)-TTF (13) by Rovira et al 75 An extension of the %-moiety for TTP compounds is also effective to improve conductivity.…”
Section: Neutral Closed Shell Moleculementioning
confidence: 99%
“…The transport properties of a few single crystals of neutral TTF derivatives have been measured, showing semiconductor character with a roomtemperature conductivity on the order of 10 -5 S/cm. [8][9][10] Additionally, organic thin films of TTF derivatives have been grown by vacuum deposition techniques, but only their morphology and nanomechanical properties have been studied. 11 However, TTF derivatives have never been used for the preparation of OFETs despite the fact that they are soluble in various solvents, easily chemically modified, and good electron donors.…”
mentioning
confidence: 99%